Plasma Cell–Free DNA Profiling of PTEN-PI3K-AKT Pathway Aberrations in Metastatic Castration-Resistant Prostate Cancer. (2021) - Kwan, Edmond M.; Dai, Chao; Fettke, Heidi; Hauser, Christine; Docanto, Maria M.; Bukczynska, Patricia; Ng, Nicole; Foroughi, Siavash; Graham, Lisa-Jane K.; Mahon, Kate; Tan, Winston; Wang, Xiaohong; et al.
Abstract : PURPOSE: Tumor tissue from metastatic castration-resistant prostate cancer (mCRPC) harbors frequent copy number variations (CNVs) in the PTEN-PI3K-AKT pathway. However, identifying CNVs in plasma cell–free DNA (cfDNA) has proven to be challenging. With emerging data supporting Akt inhibition in PTEN-deficient mCRPC, we profiled PTEN-PI3K-AKT pathway aberrations in patients with mCRPC using a novel cfDNA assay optimized for CNV detection. METHODS: A next-generation sequencing–based cfDNA assay was used to profile 231 patients with mCRPC from two independent cohorts (Australian, n = 78; United States, n = 153). PTEN-PI3K-AKT pathway genomic aberrations were correlated with clinical outcomes, including progression-free survival and overall survival (OS). RESULTS: PTEN loss and PIK3CA gain were detected in 37% (85 of 231) and 17% (39 of 231) of patients, respectively. Poorer outcomes were observed in patients with PTEN-PI3K-AKT pathway aberrations, including those with dual PTEN loss and PIK3CA gain (hazard ratio 2.3, 95% CI 1.2 to 4.4). Cumulative CNV burden in the PTEN-PI3K-AKT and androgen receptor (AR) pathways was associated with significantly worse clinical outcomes (0 v 1 v ≥ 2 CNVs in Australian cohort: median OS 33.5 v 17.2 v 9.7 months, P < .001; 0 v 1 v ≥ 2 CNVs in US cohort: median OS 35.5 v 14.3 v 9.2 months, P < .001). Notably, 21% (31 of 146) of PTEN -neutral patients harbored alternative PTEN-PI3K-AKT pathway aberrations. CONCLUSION: PTEN-PI3K-AKT pathway CNVs were readily detected using our cfDNA assay, with the prevalence of PTEN loss comparable with tissue-based studies. Additional PTEN-PI3K-AKT pathway aberrations were found in one fifth of PTEN -neutral cases. Concurrent CNVs in the PTEN-PI3K-AKT and AR pathways portended poor survival, and identifying this high-risk patient subset for dual AR/Akt inhibition may optimize precision treatment with Akt inhibitors in mCRPC.